An Explanation of (First Round) Contributions in Public-Good Experiments - Joachim Weimann; Jeannette Brosig-Koch; Timo Heinrich; Heike Hennig-Schmidt; Claudia Keser; Christian Stahr (Center for Economic Studies and ifo Institute (CESifo), 2014)
The dynamics of behavior observed in standard public-good experiments can be explained by imperfect conditional cooperation combined with social learning (Fischbacher and Gächter, 2010). But it is unclear what determines first-round contributions. We argue that first-round contributions depend on the difference between the actual marginal per capita return (MPCR) and the minimal MPCR necessary to create a social dilemma for the given group size. We use a novel connected-lab design that allows members of large groups to simultaneously interact under laboratory conditions. In total, 5,220 subjects participated in our experiment in groups of up to 100 subjects. The results confirm that first-round contributions increase with the MPCR distance. This effect carries over to contributions made in subsequent rounds. Our results demonstrate that small groups behave similar to large groups and that the salience of the di-lemma situation is of great importance for contributions made to the public good.
Keywords: C91; C72; 330; public-good experiments; large group size; connected-lab design; salience of the dilemma situation; social learning